2016
DOI: 10.1097/md.0000000000003056
|View full text |Cite
|
Sign up to set email alerts
|

Prolong Exposure of NSAID in Patients With RA Will Decrease the Risk of Dementia

Abstract: Rheumatoid arthritis (RA), a chronic, systemic inflammatory disorder, primarily affects joints. Several studies have indicated that early inflammation, cardiovascular disease, and depression in patients were associated with a considerably increased risk of dementia. Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used for treating RA. NSAIDs facilitate alleviating RA-associated chronic pain, inflammation, and swelling. Therefore, we conducted this nationwide study for evaluating the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…However, we have tried to use COPD as a proxy variable for cigarette smoking, which has been accepted previously in several studies. [30][31][32][33] Third, the accuracy of diagnoses based on administrative data is another issue of concern.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have tried to use COPD as a proxy variable for cigarette smoking, which has been accepted previously in several studies. [30][31][32][33] Third, the accuracy of diagnoses based on administrative data is another issue of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiologic studies showed that patients treated with NSAIDs had a decreased risk for developing AD (Breitner et al, 2009 ; Côté et al, 2012 ; Chang et al, 2016a , b ). However, this evidence was only based on observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, recent clinical trials have failed to show any positive effect of nonsteroidal anti‐inflammatory drugs (NSAIDs) in individuals at risk for AD . Therefore, the reduced risk of AD among long‐term NSAID users with chronic inflammatory diseases in previous observational studies would suggest a possible positive impact of the specific inflammatory mechanisms (eg, microglia activation) due to the inflammatory disease itself rather than the treatment. Alternatively, suppression of certain aspects of the inflammatory cascade associated with the disease and allowing other aspects to be active could have impacted β‐amyloid deposition.…”
Section: Discussionmentioning
confidence: 99%